ELEMEN VISUAL KEMASAN SEBAGAI STRATEGI KOMUNIKASI PRODUK - Ni Luh Desi In Diana Sari (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
One domain of visual communication design that can be used as a medium of communication of information in addition serves to protect the product is packaging. As a medium of communication and information, packaging is often referred to as the silent sales-man or girl, because packaging can represent, demonstrate the quality of the product without the presence of servants.In order to communicate product to the target audience required of visual element product packaging as a communication strategy. Visual elements consist of a logo to indicate the identity of the brand, the form of packaging, typography, color, and illustrations. The elements are arranged based on the principles of layout. Visual elements of the packaging are a symbol that communicates product attributes, benefits, values, culture and personality.